Morphology Control of CoC2O4·4H2O and Co3O4 Microspheres - Hu, Hanmei; Xu, Junchan; Wu, Weifei; Liu, Dongdong; Zhang, Lili; Hou, Zhengxiang (Asian Journal of Chemistry, 2013)
CoC2O4·4H2O microspheres composed of nanorods were firstly prepared through a microwave-assisted homogeneous precipitation reaction of Co(NO3)2·6H2O and (NH4)2C2O2 using NH3·H2O as a morphology control agent. Then, Co3O4 microspheres were successfully obtained by calcinating CoC2O4·4H2O microspheres at 300 ºC for 2 h, which preferably preserve the morphology of precursor. The products are characterized by X-ray diffraction, field-emission scanning electron microscopy and UV-visible absorption spectrum. CoC2O4·4H2O microspheres are comprised of numerous short nanorods with diameters of 30-60 nm and lengths of 400-800 nm. A single Co3O4 microsphere is constructed by nanoparicle-based nanorods and the minimum building block is Co3O4 nanoparticles with diameters of 20-30 nm. The growth mechanism is simply discussed.